Structure-Function Relationships in Bdd Anodes: Insights into Electrochemical Generation of Oxidants for Sulfamethoxazole Removal - Godoy-Perez, M (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
The efficiency of electrochemical advanced oxidation processes (EAOPs) strongly depends on the electrogeneration of reactive species at the anode-electrolyte interface. In this study, we systematically evaluated five commercial boron-doped diamond (BDD) anodes with varying carbon hybridization ratios (sp3/sp2), boron doping levels (500-10,000 ppm), and substrate materials (silica or niobium) to investigate their ability to generate oxidants and degrade the antibiotic sulfamethoxazole (SMX). The production of hydroxyl radicals (center dot OH), persulfate (S2O82-), and hypochlorite (ClO-) was quantified using EPR spectroscopy, UV-Vis spectrophotometry, and potentiometric titration, respectively. The results demonstrated that the composition of the anode significantly influences oxidant generation. The anode with 500 ppm B, a high sp3/sp2 ratio, and a silica substrate exhibited the highest center dot OH and persulfate production, attributed to favorable surface properties and high charge transfer resistance. In contrast, the anode with 2500 ppm B produced the highest ClO- concentrations, substantially enhancing SMX degradation in chloride-containing electrolytes. Morphological and wettability analyses revealed that increased boron doping promoted rod-like surface structures and greater hydrophobicity, facilitating the desorption of active chlorine species (ACS). SMX removal efficiency varied depending on the predominant oxidants formed: reactive oxygen species (ROS) dominated in sulfate media, whereas ACS were more effective in chloride media. These findings demonstrate how the structural and electrochemical properties of BDD anodes govern selective oxidant formation and pollutant degradation. This study provides new insights into structure-function relationships in BDD electrodes and underscores the importance of electrode design in optimizing the performance and selectivity of EAOPs for sustainable water treatment.